2021
DOI: 10.1097/eja.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of intraoperative dexmedetomidine versus saline infusion combined with goal-directed haemodynamic therapy for patients undergoing cranial surgery

Abstract: BACKGROUND By inhibiting neuroinflammation dexmedetomidine may be neuroprotective in patients undergoing cranial surgery, but it reduces cardiac output and cerebral blood flow. OBJECTIVE To investigate whether intra-operative dexmedetomidine combined with goal-directed haemodynamic therapy (GDHT) has neuroprotective effects in cranial surgery. DESIGN A double-blind, single-institution, randomised controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Most of the trials did not report on our outcomes. A total of 106 RCTs and one sub‐study of an included RCT provided data for quantitative synthesis 43–149 . Six of the included trials reported a total of 15 eligible comparisons 60,62,82,124,145,147 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the trials did not report on our outcomes. A total of 106 RCTs and one sub‐study of an included RCT provided data for quantitative synthesis 43–149 . Six of the included trials reported a total of 15 eligible comparisons 60,62,82,124,145,147 .…”
Section: Resultsmentioning
confidence: 99%
“…The decision to administer the Voluven was based on a ≥5% increase in the stroke volume index after a minifluid challenge test (100 mL crystalloid infusion within 1 minute). 11,12 A minifluid challenge test has a fluid responsiveness detection accuracy superior to that of stroke volume variation; therefore, it was applied to the GDHT group to achieve cardiac output optimization more efficiently. By comparison, the institutional fluid protocol was applied to the patients in the control group; this protocol comprised urine output replacement with crystalloid infusion and maintenance of stroke volume variation at <13% with crystalloid or colloid at attending anesthesiologist’s discretion.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to its broad sedative, anxiolytic, analgesic, sympatholytic, and stable hemodynamic profile, dexmedetomidine is now used as an adjuvant for premedication, especially in patients susceptible to preoperative and perioperative stress. More importantly, dexmedetomidine improves cognition after carotid endarterectomy, 91 reduces postoperative delirium after joint replacement surgery, 92 and attenuates postoperative disability after cranial surgery 93 pointing at its potential neuroprotective properties in a perioperative setting. Dexmedetomidine also reduces inflammatory factor expression and enhanced brain-derived neurotrophic factor (BDNF) levels.…”
Section: Intravenous Anesthetics For Neuroprotectionmentioning
confidence: 99%